Pengaruh Motivasi dan Disiplin Terhadap Produktivitas Kerja Pegawai Kantor Badan Pertanahan Nasional Kota Palembang - Muthi'ah Putri; Siti Komariah Hildayanti; Meilin Veronica (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
The purpose of this study is to analyze the influence of motivation and work discipline on employee productivity at the National Land Agency Office in Palembang City. Employee productivity is the relative work output compared to the set standards. It serves as a measure for evaluating the capability and performance of employees and provides valuable information related to human resources in a company. The research is a quantitative descriptive study using questionnaires. The sample size for this study is 60 employees at the National Land Agency Office in Palembang City. The data analysis techniques include classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. Based on the t-test results, the variable of work motivation partially has a positive and significant effect on work productivity. The significance value is 0.043 < 0.05, and the t-value is 2.067 > t-table 2.002. Similarly, the variable of work discipline partially has a positive and significant effect on work productivity. The significance value is 0.000 < 0.05, and the t-value is 3.899 > t-table 2.002. These results indicate that both work motivation and discipline have a significant impact on employee productivity. Furthermore, the simultaneous test (F-test) shows that both work motivation and discipline together have a positive and significant influence on work productivity. The obtained F-value is 10.087, while the F-table value is 3.16, with a significance level of 0.000 < 0.05. The R Square value of 0.689 or 68.9% indicates that both work motivation and discipline significantly affect employee productivity at the National Land Agency Office in Palembang City.